Nomenclature of appendiceal mucinous lesions according to the 2019 WHO Classification of Tumors of the Digestive System - Koç, Cemalettin; Akbulut, Sami; Akatlı, Ayşe Nur; Türkmen Şamdancı, Emine; Tuncer, Adem; Yılmaz, Sezai (Turkish Journal of Gastroenterology, 2020)
Background/Aims: To analysis the appendiceal mucinous lesions according to the World Health Organization (WHO) 2010 and 2019 classification of tumors of the digestive system (non-neuroendocrine tumors of the appendix vermiformis) Materials and Methods: Clinical and histopathological data of 37 patients with histopathologically proven appendiceal mucinous lesion from January 2010 to May 2019 were evaluated retrospectively. Pathology slides were re-evaluated by two pathologists according to the WHO 2010 and WHO 2019 classification of tumors of the digestive system. Results: Totally 37 patients (male:19 female: 18) aged 23 to 93 years were analyzed. Majority of the patients (75.7 %) had underwent appendectomy due to preliminary diagnosis of acute appendicitis (n=22) or periappendiceal tumoral lesions (n=9), the others (n=9) underwent incidental appendectomy. Whereas acute appendicitis was histopathologically diagnosed in 16 (43.2%) patients, perforation was diagnosed in 12 (32.4%) patients (perforation without appendicitis=3, perforation with appendicitis=6). According to WHO 2010 classification, pathology reports were prepared as follows: mucocele (n=10), mucinous cystadenoma (n=9), low-grade mucinous neoplasm (n=6), mucinous adenocarcinoma (n=5), mucosal hyperplasia + mucocele (n=3), mucosal hyperplasia (n=2), hyperplastic polyp (n=1), adenomatous polyp (n=1). On the basis of the WHO 2019 classification, pathology reports were prepared as follows: low-grade mucinous neoplasm (n=17), simple retention cysts (n=6), hyperplastic polyp (n=6), mucinous adenocarcinoma (n=5), ruptured appendiceal diverticula (n=2), sessile serrated lesion (n=1). Conclusion: The term of appendiceal mucinous lesion, which is recently introduced into medical literature is suitable to distinguish between lesions with and without malignancy potential. The WHO 2019 classification system has been an important step in simplifying the classification of non- neuroendocrine tumors of the appendix vermiformis.